Lao Substratum Influence on the Ideophones of Khorat Language - Trongdee, Thananan (Journal of Letters, 2020)
The origin of Khorat language has been a controversial issue among linguists. Three hypotheses are proposed. Firstly, Khorat is the result of the Yo system recoding to Bangkok Thai. Secondly, Khorat is a Lao dialect whose tones have been influenced by Central Thai. Thirdly, Khorat is a Lao dialect that has shifted to Thai but manifested Lao tone substratum. Most of the hypotheses, however, are based on phonological phenomena, especially the tone systems. In this article, evidence on category, structure and vocalic sound symbolism of ideophones in Khorat is proposed. It is found that some of the ideophone structures and vocalic sound symbolism in Khorat are exclusively the same as those in Lao. Therefore, the findings support the hypothesis that Khorat originated from a group of Lao speakers who had shifted their language to Thai but manifested Lao substratum influence on some ideophones.